The Influence Of Parenting Patterns On The Character Formation Of Third Grade Elementary School Students Paper’s - Karadona, Rosika Indri; Rahmawati, Rahmawati; Mudatsir, Mudatsir (Journal of Indonesian Progressive Education, 2026)
This study aims to analyze the influence of parenting styles on the character formation of third-grade students at Darul Hikmah Elementary School in Makassar. The research uses a descriptive quantitative approach with independent variables in the form of parenting styles, including authoritarian, democratic, and permissive parenting styles, and a dependent variable in the form of character formation of the students. The research population consisted of 110 students, with a sample of 55 students determined thru simple random sampling technique. Data collection was conducted using closed questionnaires and documentation, while data analysis was carried out thru instrument tests, prerequisite analysis tests, and hypothesis tests with the help of SPSS version 27.0. The research results showed that all research instruments were declared valid and reliable, and the data were normally distributed. Multiple linear regression analysis shows a significant influence of parenting styles on the character formation of students, with a coefficient of determination (R²) value of 0.955. These findings indicate that parental upbringing contributes 95.5% to the character formation of students, with democratic parenting being the most dominant style. Thus, it can be concluded that parental upbringing plays an important role in shaping the character of elementary school students and needs serious attention in efforts to strengthen character education.